2018
DOI: 10.31729/jnma.3699
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Graft Uptake and Hearing Assessment after Palisade Myringoplasty

Abstract: Introduction: Cartilage as a graft for closure of tympanic membrane has got superior benefits than other usual grafts (temporalis fascia and perichondrium). Cartilage supported myringoplasty with palisade technique has good result of graft uptake rate, even under difficult conditions. This technique brings very good functional and better long-term results. This study is done to assess graft uptake rate and hearing improvement after myringoplasty with cartilage palisade technique. Methods: It is a descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The age range of the patients was also similar to ours with more patients in the younger age groups. 10,11 Our study had a female preponderance whereas other studies showed males who were affected by the condition undergoing surgery. 11,12 Ear surgery was revolutionized initially by the introduction of the monocular microscope in 1921 and then even further in 1922 by Gunnar Holmgren who is responsible for the development of the binocular microscope.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…The age range of the patients was also similar to ours with more patients in the younger age groups. 10,11 Our study had a female preponderance whereas other studies showed males who were affected by the condition undergoing surgery. 11,12 Ear surgery was revolutionized initially by the introduction of the monocular microscope in 1921 and then even further in 1922 by Gunnar Holmgren who is responsible for the development of the binocular microscope.…”
Section: Discussionmentioning
confidence: 55%
“…10,11 Our study had a female preponderance whereas other studies showed males who were affected by the condition undergoing surgery. 11,12 Ear surgery was revolutionized initially by the introduction of the monocular microscope in 1921 and then even further in 1922 by Gunnar Holmgren who is responsible for the development of the binocular microscope. 13 This helped illuminate and magnify the surgical field while freeing up both hands to operate on the ear.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…(2023) discuss, Nepal has experimented with three diverse generations of local democracy in the last 70 years. The first generation (before the 1960s) involved an evolutionary local democratic practice in which the central government exercised excessive power to determine boundaries, structures, and leaders (or Panchas) to form local governments (KC, 1976). The second generation (1960–1990) advanced the development of local democracy in Nepal by promulgating legislation to establish rural and urban municipalities, although such legislation is always contested in terms of its democratic quality (Dharamdasani, 1984).…”
Section: Literature Reviewmentioning
confidence: 99%